The lyrics of the songs “Coco livre” and “Taquarulua”- poetry, culture and imaginary - Almeida, Juliana Santana de (2022)
This article analyzes the lyrics of the songs “Coco Livre”, on the CD Brasís: as canções e o povo (1998), by Genésio Tocantins, and “Taquarulua”, on the CD Taquarulua (2009), by Dorivã, exploring the words that relate to local culture, poetry and the imaginary of Tocantins. Genésio Tocantins began his musical career in the 1970s and Dorivã a decade later, around the 1980s. The two artists have been active in the art and culture of the state of Tocantins for over 40 years, participating in and winning several song festivals in the state and around Brazil, as well as being invited to international events to represent Tocantins and the Brazilian music. The guiding question asks whether the lyrics of the analyzed songs address regional themes and can be considered representatives of regional music. Following on from this, it is our intention to discuss how these themes can be acknowledged as identity and cultural representations present in the imaginary of the state of Tocantins. The main objective is to present the two Tocantins musicians and their musical productions, specifically the lyrics of the songs mentioned above. The theorists that support this reflection are: Cândido (1995), Compagnon (2001), Hall (2015), and Moraes (2000).